Dairy foods : processing, quality, and analytical techniques - Cruz, Adriano Gomes da; Ranadheera, C. Senaka; Nazzaro, Filomena; Mortazavian, Amir M. (Woodhead Publishing, 2022)
Dairy Foods: Processing, Quality, and Analytical Techniques provides comprehensive knowledge on the different factors involved in the development and safety precautions behind dairy foods, including special references to both theoretical and practical aspects. The book presents relevant information about the quality of dairy foods, including raw milk quality, predictive microbiology and risk analysis, food defense and food fraud. In addition, it looks into environmental aspects and consumer perception and goes on to cover methods and practices to process dairy products and analytical techniques behind dairy product development. Techniques explored include time domain magnetic resonance, thermal analysis and chemometric methods. This will be a valuable resource for researchers and practitioners in the dairy industry, as well as students in dairy science courses.